Kathryn Shipley - Unidentified photographer (Colorado State University. Libraries, 1987)
Photograph of Kathryn Shipley, standing next to her teal dress displayed on a mannequin in the "Old Beginnings" exhibit, held in the Gustafson Gallery. She donated this dress to the historic clothing collection. In the background is a textile hung on the wall.
Keywords: Fashion -- History; Fashion -- Exhibitions